Are computer‐based interventions effective for decreasing symptoms in adolescents with major depression?. Issue 3 (March 2015) - Pence, Megan; Rowland, Kate
Abstract : Evidence‐Based Answer : One computer‐based intervention (SPARX) is at least as effective as usual care for decreasing depressive symptoms in adolescents. Another intervention (MoodGYM) has limited efficacy for adolescent boys, but may be effective for teenage girls (SOR: B, individual nonrandomized controlled trials).